Efektivitas Program Induksi Di SD Negeri Temperak Dalam Meningkatkan Kinerja Dan Profesionalisme Pendidikan - Tumeko, Dwi Satrio Bagus; Sugiharti, Sugiharti; Arifin, Ahmad Zaenal; Nurkolis, Nurkolis (Jayapangus Press, 2025)
This study aims to analyze the effectiveness of the induction program for teachers and school principals at SD Negeri Temperak in improving performance and educational professionalism. The approach used is a descriptive qualitative method, with data collection through interviews, observations, and documentation. The results of the study indicate that the induction program has been effective in helping new teachers and school principals adapt to their work environment. New teachers who participated in this program experienced increased self-confidence and teaching skills, enabling them to deliver more optimal lessons to students. On the other hand, new school principals gained a better understanding of school management and leadership, which contributed to the improvement of overall school management effectiveness. However, the implementation of the induction program at SD Negeri Temperak still faces several challenges, such as the lack of experienced mentors, limited time, and minimal support from the local government. To address these challenges, this study suggests several strategies, including specialized training for mentors, the use of online learning platforms, more flexible mentoring schedules, and increased collaboration with the local education office to gain better policy and budget support. By implementing these strategies, it is expected that the induction program can run more effectively and sustainably, ultimately improving the quality of education at SD Negeri Temperak.